Comparative cytology of the infection process of Colletotrichum sublineola falcate and oval conidia in susceptible and resistant sorghum cultivars (Research, Society and Development, 2020)
The primary infection mode of Colletotrichum sublineola, the causal agent of anthracnose in sorghum, occurs through falcate conidia produced blasticaly from conidiophores in acervuli. A secondary type of conidium, the oval conidium, smaller in size and distinct ontogeny from the falcate ones, is also produced by this pathogen. The objective of this study was to compare, by light microscopy, the infection process between both conidia, the ovals and falcados conidia from C. sublineola, in resistant and susceptible sorghum cultivars to anthracnose. Leaves of sorghum plants with 25 days old from BR009 (susceptible) and SC283 (resistant) cultivars were detached and inoculated with both conidia obtained from 204.01 pathogenic isolate and the process of infection was observed by optical microscopy between 2 to 168 hours after inoculation (AI). Both conidia germinated 2 hours AI and, regardless of the cultivar, after 4 hours AI, rounded appressoria with smooth surface were formed directly from the falcate conidium, while slightly irregular appressoria were formed at the tip of the germinative tubes emitted by the oval conidia. At the susceptible cultivar, appressoria were formed with higher frequency by falcate conidia, while at the resistant cultivar these structures were formed with higher frequency by the oval conidia. Penetration pores and infection hyphae were observed in all the inoculated materials with both conidia. Disease symptoms were observed first on the inoculated material with falcate conidia and mainly on the susceptible cultivar. Lesions with acervuli containing falcate conidia were found at all treatments, thus completing the infection cycle.